Direct genotyping of Mycobacterium tuberculosis from Xpert® MTB/RIF remnants. (July 2018) - Mambuque, Edson T.; Abascal, Estefanía; Venter, Rouxjeane; Bulo, Helder; Bouza, Emilio; Theron, Grant; García-Basteiro, Alberto L.; García-de-Viedma, Darío
Abstract: Genotyping of Mycobacterium tuberculosis (MTB) isolates has markedly improved our knowledge of its transmission dynamics. MIRU-VNTR is considered the reference molecular tool for MTB fingerprinting. However, the dependence of this technique on cultured isolates means that we lack molecular epidemiology data from many settings where culture facilities have not been implemented. Efforts have been made to adapt the MIRU-VNTR procedure to direct analysis of clinical specimens, although implementation of these efforts has not proven successful. The large-scale roll-out of Xpert MTB/RIF (Xpert) technology, which is now in almost every TB-endemic country, including many where MTB is not cultured, provides us with a new opportunity to explore whether MTB genotyping could be performed from the remnants of the Xpert cartridge. We ran a pilot study in Mozambique in which the remnants of 24 positive Xpert assays for detection of MTB were used as template material for the 15-locus or the more discriminatory 24-locus MIRU-VNTR technique. MTB fingerprinting was possible in specimens with a high bacterial burden, according to the Xpert load categories, and within the first week after Xpert was performed. Given the wide availability, simple processing, and rapid reporting of results with Xpert, our findings suggest that MIRU-VNTR–based fingerprinting from remnants of Xpert could play a major role in extending MTB molecular epidemiology studies to settings where information on the transmission dynamics of this pathogen is lacking.